2003
DOI: 10.1001/jama.289.16.2094
|View full text |Cite
|
Sign up to set email alerts
|

Decreased β-Amyloid1-42and Increased Tau Levels in Cerebrospinal Fluid of Patients With Alzheimer Disease

Abstract: HILE THE EXACT BIOLOGIcal cascade associated with Alzheimer disease (AD) is only partially understood, many potential biomarkers of this disease process are known. 1 Two of the most obvious candidates are ␤-amyloid 1-42 and tau proteins, as they are intimately related to the pathognomonic features of amyloid plaques and neurofibrillary tangles in the AD brain. 2,3 Multiple previous studies have reported decreases in cerebrospinal fluid (CSF) measures of ␤-amyloid. 4-7 Similarly, CSF measures of tau have routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
389
4
14

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 606 publications
(448 citation statements)
references
References 74 publications
41
389
4
14
Order By: Relevance
“…The diagnostic performance of the three biomarkers, total tau, phospho-tau, and the 42 amino acid form of ␤-amyloid have been evaluated in numerous studies and their ability to identify incipient AD in MCI cases has also been studied. Some candidate AD biomarkers including ubiquitin, neurofilament proteins, growth-associated protein 43 (neuromodulin), and neuronal thread protein (AD7c) show interesting results but have been less extensively studied. It is concluded that CSF biomarkers may have clinical utility in the differentiation between AD and several important differential diagnoses, including normal aging, depression, alcohol dementia, and Parkinson's disease, and also in the identification of Creutzfeldt-Jakob disease in cases with rapidly progressive dementia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnostic performance of the three biomarkers, total tau, phospho-tau, and the 42 amino acid form of ␤-amyloid have been evaluated in numerous studies and their ability to identify incipient AD in MCI cases has also been studied. Some candidate AD biomarkers including ubiquitin, neurofilament proteins, growth-associated protein 43 (neuromodulin), and neuronal thread protein (AD7c) show interesting results but have been less extensively studied. It is concluded that CSF biomarkers may have clinical utility in the differentiation between AD and several important differential diagnoses, including normal aging, depression, alcohol dementia, and Parkinson's disease, and also in the identification of Creutzfeldt-Jakob disease in cases with rapidly progressive dementia.…”
Section: Resultsmentioning
confidence: 99%
“…A moderate to marked decrease in CSF A␤42 in AD to about 50% of control levels has been found using the majority of these methods (Table 1). 35,39,[41][42][43][44][45]47,48 An increase in CSF A␤42 in AD was found in one study. 46 This finding may be attributable to methodological differences (e.g., assay specificity for aggregated or truncated A␤ variants).…”
Section: ␤-Amyloidmentioning
confidence: 88%
See 1 more Smart Citation
“…CSF biomarkers have proven to be the most accurate of the biomarkers investigated to date, with AD being shown to be associated with decreased Aβ42 levels and increased tau levels in the CSF [33]. However the latter procedure is invasive and patient compliance is anticipated to be low.…”
Section: Diagnosismentioning
confidence: 99%
“…Por meio de uma metanálise, Sunderland et al (2003) examinaram os achados de 17 artigos sobre Aβ42 e 34 artigos sobre tau no LCR de pacientes com DA. Todos os estudos incluídos nessa metanálise relataram aumento de tau total no LCR na DA.…”
Section: Proteína Tau E Suas Formas Fosforiladasunclassified